2020
DOI: 10.1002/adma.202000091
|View full text |Cite
|
Sign up to set email alerts
|

Multicompartment Tubular Micromotors Toward Enhanced Localized Active Delivery

Abstract: A tubular micromotor with spatially resolved compartments is presented towards efficient sitespecific cargo delivery, with a back-end zinc (Zn) propellant engine segment and an upfront cargo-This article is protected by copyright. All rights reserved. 2 loaded gelatin segment further protected by a pH-responsive cap. The multi-compartment micromotors display strong gastric-powered propulsion with tunable lifetime depending on the Zn segment length. Such propulsion significantly enhances the motor distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 35 publications
0
83
0
Order By: Relevance
“…Here, a compartmentalized MBR would be used. It would contain a cargo-carrying cap, similar to the previously described work of Esteban-Fernandez de Avila et al ( Figure 4 C) [ 46 ]. For in vivo applications, the MBR’s cargo-carrying cap could even be functionalized to target the endothelial lining of the pulmonary vasculature, and would only release the contained Cpd22 upon detection of chemical markers indicating penetration of the extracellular matrix and localization with the fusion with the contained SMCs [ 45 ].…”
Section: Organ-on-a-chip Disease Models For Microbiorobot-assistedmentioning
confidence: 67%
See 2 more Smart Citations
“…Here, a compartmentalized MBR would be used. It would contain a cargo-carrying cap, similar to the previously described work of Esteban-Fernandez de Avila et al ( Figure 4 C) [ 46 ]. For in vivo applications, the MBR’s cargo-carrying cap could even be functionalized to target the endothelial lining of the pulmonary vasculature, and would only release the contained Cpd22 upon detection of chemical markers indicating penetration of the extracellular matrix and localization with the fusion with the contained SMCs [ 45 ].…”
Section: Organ-on-a-chip Disease Models For Microbiorobot-assistedmentioning
confidence: 67%
“…Schuerle et al used helical swimming microrobots to enhance convective transport of fluorescent nanoparticles across a vessel–matrix interface representative of blood vessel extravasation ( Figure 4 B) [ 45 ]. Alternately, Esteban-Fernandez de Avila et al created an active transport-based system and incorporated a propulsive motor in a multicompartment microstructure to aid in physically penetrating a tissue barrier ( Figure 4 C) [ 46 ]. In this case, the drug of interest was encapsulated in a pH-responsive cap, which only began to dissolve upon penetration of the tissue lining, which exposed the cap to an increased pH.…”
Section: Microbiorobots: Motility In Fluid Environments and Penetrmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with the results derived from previous toxicity studies using Zn-based microrockets in the same mouse model. [13,14] Overall, the in vivo toxicity studies of Zn microrocket pills showed no apparent alteration of GI histopathology and no observable inflammation, suggesting that the pill treatment at the administered Zn microrocket dosage is safe in mice. It is important to mention that increasing the content of Zn microrockets beyond 10% might produce abnormal GI inflammation due to excessive H 2 gas generation.…”
Section: Zn Microrocket Pill Toxicity Studymentioning
confidence: 92%
“…[11] Different designs of such acid-powered Znmicrorockets have demonstrated efficient cargo-loading capacity with autonomous release. [12,13] One of the key advantages of Zn-based microrockets is the biodegradability of the motor body, which completely dissolves and disappears in acidic conditions, thus leaving no harmful products behind. Such biodegradable behavior along with efficient propulsion in the gastric fluid has led to the first in vivo demonstration of Zn-based microrockets in a mouse model, illustrating a greatly enhanced retention of the payloads in the stomach lining without causing toxic effects.…”
Section: Introductionmentioning
confidence: 99%